Aplikasi Penomoran Dan Penyimpanan Surat dengan metode AES dan RSA berbasis WEB - Aziz, Topaz Malik; Dwiasnati, Saruni (Jurnal Tata Kelola dan Kerangka Kerja Teknologi Informasi, 2023)
The purpose of this research is to secure data by applying encryption to ensure the security and confidentiality of letter documents with the application of letter numbering and storage. Organizations that have many work units and often correspond with customers and or partners need an application system that prevents errors in letter numbering and controls access rights, especially information that can only be known by certain parties. In an organization it is often found that the numbering of documents is not neat and the document storage is not centralized and is generally stored on the employee's local device. Data security and document confidentiality are insecure and cannot be controlled centrally. Such as document minutes, outgoing letters and POs. Therefore to improve and guarantee security, efficiency and facilitate an organization in correspondence activities so that mail is stored. Numbering and letter storage applications are made using the C# programming language and SQL Server database, and with the implementation of a combined encryption algorithm of AES and RSA encryption so that the stored data is guaranteed data security and centralized data storage.